Seismic Damage Assessment and Retrofitting of Hybrid Structure - Inderyas, O.; Ilyas, U.; Farooq, S. H.; Ajwad, A.; Khadim, N. (The Nucleus, 2020)
Pakistan is highly seismically prone country, which faced devastated earthquakes in history. The hybrid structures are very common in northern areas of Pakistan and their behavior under seismic event is very critical. The Seismic response of hybrid buildings is different from other structural systems as there is discontinuity, both in the lateral and vertical load transfer mechanisms. To assess the seismic damage of hybrid building for zone 2B and 3, the pushover analysis was carried out on a 6 story sample building with its 4 bottom stories of reinforced concrete frame and top two stories of steel frames for a maximum drift of 2.5%. Pushover analysis was performed using commercial software SAP2000 v15 and critical seismic deficiencies were determined. Basing on the identified deficiencies in stiffness as well as the ductility a comprehensive retrofit design was carried out. The hybrid building was retrofitted with shear walls and steel brace to remove the deficiencies in stiffness and ductility. After retrofitting pushover analysis was again carried out to determine the efficacy of retrofit design. The results revealed that retrofit intervention significantly improved the seismic performance of the hybrid building and increased the stiffness / lateral capacity by 47% and 42% respectively. Moreover, lateral displacements was also reduced by 37% and 42% by adding shear walls and braces respectively. The research outcome will help the local engineers and designers to properly retrofit the existing buildings in Northern Areas of Pakistan.